Manual de Procedimientos para el programa de Becas de la sección de Trabajo Social, del Departamento del DEVESA del Tecnológico de Costa Rica, Sede Regional San Carlos - Chacón-Corrales, Ana Sofía (Instituto Tecnológico de Costa Rica, 2015)
This project shows as main objective to develop a manual of procedures to facilitate the proper and accurate operation Section of Social Work DEVESA Tecnologico of Costa Rica, San Carlos Regional. It also objectives to analyze the current procedures by lifting procedures, making the performance of the documentation of each to make a proposal for implementation. To collect information, in order to achieve the objectives a poll and observation for lifting procedures are used. The survey is based on an unstructured interview and a questionnaire for the analysis of processes. Procedures were documented, corresponding section Social Work scholarships because not had a manual of procedures that facilitate the function of the professional counseling. It is important that this manual process is implemented and that all procedures are performed at least one publication of results.
Proyecto de graduación (Bachillerato en Administración de Empresas) Instituto Tecnológico de Costa Rica, Escuela Administración de Empresas, 2015
Keywords: Beca universitaria; Manual de procedimientos; Departamento Vida Estudiantil y Servicios Académicos